New Paradigm Concept Of Economic Growth In Islamic Perspective - Jasman Saripuddin Hsb, S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
New Paradigm Concept Of Economic Growth In Islamic Perspective